Thayib standardization for Muslim friendly public worship facilities in Indonesia - Rulindo, Ronald; Purnama, Fadhil Akbar; Rosida, Rosviana (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – This study aims to determine the ideal standardization of public worship facilities in Muslim-friendly tourist destinations as the availability of those facilities, such as prayer rooms and toilets, is very important for Muslim tourists. Methodology – This study uses a factor analysis approach. Samples were obtained using a convenience sampling technique, with a total sample of 326 respondents from various provinces throughout Indonesia. The process was carried out after going through a focus group discussion (FGD) as a screening stage for the questions used in the quantitative analysis. Findings – The results of this study indicate that there are two recommended factors for the standardization of prayer facilities and four for the standardization of toilet facilities. Implementing these factors affects tourists' intentions to revisit destinations or recommend such destinations to other travelers. Implications – This research is believed to be authentic because it offers a model of standardization of public facilities in Muslim-friendly tourism areas for the halal industry, as well as provides a comprehensive review of the underlying literature. Thus, this study is expected to have a significant impact on both practical and theoretical knowledge.Originality – This research is considered original and important for both practice and theory fields to provide a standardization that can be applied especially for Muslim-friendly tourism.